The Influence of Functional Shoulder Biomechanics as a Mediator of Patient-Reported Outcomes following Mastectomy and Breast Reconstruction. Issue 1 (2nd October 2020) - Leonardis, Joshua M.; Lyons, Daniel A.; Kidwell, Kelley M.; Giladi, Aviram M.; Lipps, David B.; Momoh, Adeyiza O.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Postmastectomy breast reconstruction techniques differentially influence patient-reported physical and psychosocial well-being. Objective measures of shoulder biomechanics, which are uniquely influenced by reconstruction technique, may provide insight into the influence of reconstruction technique on patient-reported outcomes. Methods: Robot-assisted measures of shoulder strength and stiffness, and five validated patient-reported outcomes surveys were obtained from 46 women who had undergone mastectomy and a combined latissimus dorsi flap plus subpectoral implant, subpectoral implant, or DIEP flap breast reconstruction. Mediation analyses examined the role of functional shoulder biomechanics as a mediator between reconstruction technique and patient-reported outcomes. Results: Reconstruction technique affected shoulder biomechanics, with latissimus dorsi flap plus subpectoral implant patients exhibiting reduced shoulder strength and stiffness compared with subpectoral implant and DIEP flap patients. Increasing external rotation strength was predictive of improved upper extremity function (p = 0.04). Increasing shoulder stiffness while at rest was predictive of worsened upper extremity function (p = 0.03). Increasing shoulder stiffness at rest and during contraction was indicative of worsened psychosocial well-being (all p ≤ 0.02). Reconstruction technique did not predict survey scores of function directly, or when mediated by functional shoulder biomechanics. Conclusions: In the current cohort, latissimus dorsi plus subpectoral implant breast reconstructions significantly reduced shoulder strength and stiffness when compared with the other techniques. In addition, objective measures of shoulder biomechanics were predictive of patient-reported physical and psychosocial well-being. The results emphasize the need for improved perioperative screening for shoulder functional deficits in patients undergoing breast reconstruction. CLINICAL QUESITON/LEVEL OF EVIDENCE: Therapeutic, II.